Retrograde crossing stent placement strategies at the basilar apex for the treatment of wide necked aneurysms: reconstructive and deconstructive opportunities. (5th October 2009) - Pride, G L; Welch, B; Novakovic, R; Rickert, K; White, J; Dutton-Johnson, K; Samson, D; Purdy, P
Abstract : Neck remodeling devices such as the Neuroform or Enterprise greatly facilitate the endovascular treatment of wide necked basilar apex aneurysms. The complex anatomy of the basilar apex affords opportunity for antegrade, multiple crossing and retrograde device placement strategies to facilitate coil embolization. A retrograde approach is possible in the presence of a posterior communicating artery large enough to allow device navigation. Our experience with a retrograde device placement strategy in three patients is reported. In two patients, device positioning extended from one P1 segment of the posterior cerebral artery to the other across the basilar apex. In one patient, device positioning extended from the P1 segment of the posterior cerebral artery across the basilar apex into the opposite superior cerebellar artery. All patients underwent reconstructive or deconstructive uncomplicated coil embolization after device placement with stable aneurysm occlusion on follow-up angiography. In appropriate anatomic situations, retrograde stent placement across the basilar apex through a posterior communicating artery may represent a preferred strategy for wide necked basilar apex aneurysms.